2022
DOI: 10.1097/cd9.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Challenges of Valvular Heart Disease Interventional Therapy

Abstract: Valvular heart disease (VHD) is common in the global population, occupying an heavy disease burden among aging population. Currently, it is the booming era of transcatheter VHD treatment, even with superiority than traditional open heart surgery in some clinical outcomes. We collected data sources mainly derived from published articles and conference presentations, including randomized controlled trials, first-in-man studies, clinical registries, and other single-or multi-center and prospective or retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…Especially in China, to date, 95% of patients are clinically treated with self-expanding valves, and even the expert consensus on treatment is for SEV ( 11 ). SAPIEN 3 Transcatheter Aortic BEV System was approved by the National Medical Products Administration in China just since June 2020 ( 12 ). A study at Fu Wai Hospital in China showed a high safety and efficacy profile for BEV (SAPIEN 3) and SEV, with no significant difference, however, the number of BEV cases in this study was small ( n = 25) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially in China, to date, 95% of patients are clinically treated with self-expanding valves, and even the expert consensus on treatment is for SEV ( 11 ). SAPIEN 3 Transcatheter Aortic BEV System was approved by the National Medical Products Administration in China just since June 2020 ( 12 ). A study at Fu Wai Hospital in China showed a high safety and efficacy profile for BEV (SAPIEN 3) and SEV, with no significant difference, however, the number of BEV cases in this study was small ( n = 25) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%